Crashworthiness optimization of new thin-walled cellular configurations. Issue 5 (1st July 2014) - Hou, Shujuan; Zhang, Zhidan; Yang, Xujing; Yin, Hanfeng; Li, Qing
Abstract : Purpose: – The purpose of this paper is to optimize a new thin-walled cellular configurations with crashworthiness criteria, so as to improve the crashworthiness of components of a vehicle body. Design/methodology/approach: – ANSYS Parametric Design Language is used to create the parameterized models so that the design variables can be changed conveniently. Moreover, the surrogate technique, namely response surface method, is adopted for fitting objective and constraint functions. The factorial design and D-optimal criterion are employed to screen active parameters for constructing the response functions of the specific energy absorption and the peak crushing force. Finally, sequential quadratic programming-NLPQL is utilized to solve the design optimization problem of the new cellular configurations filled with multi-cell circular tubes under the axial crushing loading. Findings: – Two kinds of distribution modes of the cellular configurations are first investigated, which are in an orthogonal way and in a diamond fashion. After comparing the optimized configurations of the rectangular distribution with the annular distribution of the multi-cell fillers, it is found that the orthogonal way seems better in the aspects of crashworthiness than the diamond fashion. Originality/value: – The two new thin-walled cellular configuration are studied and optimized with the crashworthiness criteria. Study on the new cellular configurations is very valuable for improving the crashworthiness of components of a vehicle body. Meanwhile, the factorial design and the factor screening are adopted in the process of the crashworthiness optimization of the new thin-walled cellular configurations.